A proper noun in artificial languages: theoretical and practical aspects - Yuliya V. Kalugina, Andrey N. Belyaev, Olga N. Novikova, Alfiya F. Aznabaeva, (Opción, 2020)
The article is devoted to the study of proper nouns in artificial languages. The use of the comparative method in the study of proper nouns in artificial languages of different types allowed to determine the degree of their representation and identify their general characteristics – onomastic universals. The result of the pioneering research was the primary classification of artificial languages according to the representation of proper nouns (anthroponyms and toponyms), which set a new vector for their study. In conclusion, in languages aimed at facilitating international intercultural interaction, the original proper nouns are maximally preserved, slightly adapting to morphophonology